2018
DOI: 10.3390/ijerph15091976
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Shapley Value Method for a Green Supply Chain Income Distribution Mechanism

Abstract: Low-carbon development and environmental remediation are key factors for green resource-based supply chains in China. With this aim in mind, by applying game theory under uncertain market demand, this paper incorporates low-carbon development and environmental remediation into a resource-based supply chain coordination model for decentralized and centralized markets. The results show that a centralized market can lead to improvement in total profit. Furthermore, based on an improved Shapley value method, a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The most important considerations that should be applied to modify the Shapley value in supply chain are the players' risk, contribution and input to the supply chain coalition (Xu et al, 2014;. Gao and Shi (2010) and Xu et al (2018) stated that the Shapley value assumes that the players in a coalition have identical risks and must face different risk occurrences and severities to gain profit and provide contribution to the coalition. On the contrary, value added also has high contribution that reflects supply chain stakeholders' performance.…”
Section: Cooperative Game Theory: the Shapley Value And Its Limitationsmentioning
confidence: 99%
“…The most important considerations that should be applied to modify the Shapley value in supply chain are the players' risk, contribution and input to the supply chain coalition (Xu et al, 2014;. Gao and Shi (2010) and Xu et al (2018) stated that the Shapley value assumes that the players in a coalition have identical risks and must face different risk occurrences and severities to gain profit and provide contribution to the coalition. On the contrary, value added also has high contribution that reflects supply chain stakeholders' performance.…”
Section: Cooperative Game Theory: the Shapley Value And Its Limitationsmentioning
confidence: 99%
“…Based on equations (12)- (17), we can obtain the optimal decisions of advertising investment and subsidy. When M chooses not to label, we can derive c N *…”
Section: Proposition 7 Table 5 Presents the Optimal Decisions Of Plamentioning
confidence: 99%
“…Second, it supposes that all enterprises bear the same risk, but certain factors, such as ecological technology level and risk, will also affect profit allocation. In view of this context, Xu et al [17] took into account the environmental effort level and risk to improve the Shapley value method.…”
Section: Introductionmentioning
confidence: 99%
“…Using game theory, Esmaeili et al [28] constructed two extended service models under different supply chains and discussed the dominant decision-making problems of the market participants in the product market and the warranty market under a decentralized decision-making mechanism of supply chain. Xu et al [29] considered the issue of bundled pricing of durable consumer goods with warranty services under monopoly and duopoly market structures. Based on the above literature on warranty decision making, it is found that there are few studies on the coordination of supply chain systems when strong retailers provide extended warranty services.…”
Section: Warranty Operational Decisionsmentioning
confidence: 99%